The impact of oil prices and the financial market on cost efficiency in the insurance and Takaful sectors: evidence from a stochastic frontier analysis - Alshammri, Ahmad Alrazni; Syed Jaafar Alhabshi, Syed Musa; Saiti, Buerhan (Elsevier B.V., 2019)
The Gulf Cooperation Council's (GCC) insurance industry, including conventional insurance and Takaful, has witnessed remarkable growth during the last decade. However, the economies of this region rely on oil as the primary stream of revenue and lack development in financial markets. This could affect the insurance industry. For this reason, this paper examines the impact of oil prices and the financial market on the cost efficiency of the insurance and Takaful sectors in GCC countries using a stochastic frontier cost function with data from 2009–2016. The results show that the relationship between oil prices and efficiency changes from positive to negative when the prices increase, whereas the relationship between the financial market and efficiency is negative. No clear evidence of the impact of oil prices on efficiency arises from the differences between conventional insurance and Takaful. However, there are differences regarding the financial market, with a negative impact on conventional insurance and a positive one on the Takaful business. The results of this study have implications for regulators and management. The Takaful industry is rapidly growing compared to conventional insurance in the GCC and, therefore, the financial market may have added benefits for the GCC region. However, caution is required in relation to the impact of the financial market on conventional insurance. Furthermore, management may require the development of strategies to deal with the nature of GCC economies to avoid shocks to oil prices. © 2019